Distinct modes of meltwater drainage and landform development beneath the last Barents Sea ice sheet - Shackleton, Calvin; Patton, Henry; Winsborrow, Monica; Esteves, Mariana; Bjarnadóttir, Lilja; Andreassen, Karin (Frontiers in Earth Science, 2023)
The flow of glacial ice is impacted by basal meltwater drainage systems that fluctuate on a continuum from distributed, high-pressure environments to channelized, lower pressure networks. Understanding the long-term development of dominant drainage modes and impacts on ice flow and landform development is a crucial step in predicting palaeo and contemporary ice-mass response to changes in climate. The spatial and temporal scales at which different drainage modes operate are largely unknown, and the geomorphological legacy of subglacial meltwater networks that evolve over a glaciation provide composite records of drainage system development. Here, we use high-resolution bathymetric data from shallow banks in the central Barents Sea to map the geomorphological imprint of meltwater drainage beneath the collapsing marine-based Barents Sea Ice Sheet (BSIS). We observe a succession of distinct meltwater landforms that provide relative timing constraints for subglacial drainage modes, indicating that extensive networks of channelized drainage were in operation during deglaciation. Interlinked basins and channels suggest that meltwater availability and drainage system development was influenced by filling and draining cycles in subglacial lakes. Networks of eskers also indicate near-margin meltwater conduits incised into basal ice during late-stage deglaciation, and we suggest that these systems were supplemented by increased inputs from supraglacial melting. The abundance of meltwater during the late stages of BSIS deglaciation likely contributed to elevated erosion of the sedimentary substrate and the mobilisation of subglacial sediments, providing a sediment source for the relatively abundant eskers found deposited across bank areas. A newly discovered beaded esker system over 67 km long in Hopendjupet constrains a fluctuating, but generally decelerating, pace of ice retreat from ∼1,600 m a−1 to ∼620 m a−1 over central Barents Sea bank areas during a 91-year timespan.